Investigating people’s attitudes towards participating in longitudinal health research: an intersectionality-informed perspective - Merz, Sibille; Jaehn, Philipp; Pischon, Tobias; Fischer, Beate; Wirkner, Kerstin; Rach, Stefan; Guenther, Kathrin; Obi, Nadia; Holmberg, Christine (International journal for equity in health, 2023)
Background Increasing evidence suggests that participation proportions in longitudinal health research vary according to sex/gender, age, social class, or migration status. Intersectionality scholarship purports that such social categories cannot be understood in isolation and makes visible the co-dependent nature of the social determinants of health and illness. This paper uses an intersectionality-informed approach in order to expand the understanding of why people participate in health research, and the impact of intersecting social structures and experiences on these attitudes. Methods A sample of 80 respondents who had previously either accepted or declined an invitation to participate in the German National Cohort (NAKO) participated in our interview study. Interviews were semi-structured and contained both narrative elements and more structured probes. Data analysis proceeded in two steps: first, the entire data set was analysed thematically (separately for participants and non-participants); second, key themes were compared across self-reported sex/gender, age group and migration status to identify differences and commonalities. Results Respondents’ attitudes towards study participation can be categorised into four themes: wanting to make a contribution, seeking personalised health information, excitement and feeling chosen, and seeking social recognition. Besides citing logistical challenges, non-participants narrated adverse experiences with or attitudes towards science and the healthcare system that deterred them from participating. A range of social experiences and cultural value systems shaped such attitudes; in particular, this includes the cultural authority of science as an arbiter of social questions, transgressing social categories and experiences of marginalisation. Care responsibilities, predominantly borne by female respondents, also impacted upon the decision to take part in NAKO. Discussion Our findings suggest that for participants, health research constitutes a site of distinction in the sense of making a difference and being distinct or distinguishable, whereas non-participants inhabited an orientation towards science that reflected their subjective marginalisation through science. No clear relationship can thereby be presumed between social location and a particular attitude towards study participation; rather, such attitudes transgress and challenge categorical boundaries. This challenges the understanding of particular populations as more or less disadvantaged, or as more or less inclined to participate in health research.